2009
DOI: 10.1093/sleep/32.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Continuous Positive Airway Pressure Therapy on Inflammation Markers of Patients with Obstructive Sleep Apnea Syndrome

Abstract: The selective reduction of soluble and cellular immune response factors only in those OSAS patients who exhibited good compliance to CPAP therapy provides further evidence for an ongoing systemic immune process in OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 23 publications
3
76
0
Order By: Relevance
“…Our group and others have shown a gradual decrease of CRP levels with effective PAP therapy, which could subsequently improve cardiovascular morbidity associated with OSAS [19,[65][66][67][68][69] , whereas others found that PAP therapy did not significant change CRP levels, regardless of PAP therapy duration [39,42,65,[70][71][72][73][74] . Furthermore our study [60] showed that after PAP therapy CRP was decreased more slowly in females compared to matched for OSAS severity males.…”
Section: Effect Of Positive Airway Pressure Therapy On Levels Of Crpmentioning
confidence: 66%
“…Our group and others have shown a gradual decrease of CRP levels with effective PAP therapy, which could subsequently improve cardiovascular morbidity associated with OSAS [19,[65][66][67][68][69] , whereas others found that PAP therapy did not significant change CRP levels, regardless of PAP therapy duration [39,42,65,[70][71][72][73][74] . Furthermore our study [60] showed that after PAP therapy CRP was decreased more slowly in females compared to matched for OSAS severity males.…”
Section: Effect Of Positive Airway Pressure Therapy On Levels Of Crpmentioning
confidence: 66%
“…21) And another research reported that TNF-α and IL-6 levels were decreased in OSA patient after surgical treatment and IL-6 level showed more improvement than TNF-α. Elevated TNF-α level predicts the incidence of cardiovascular event in several conditions like heart failure and acute coronary syndrome.…”
Section: )mentioning
confidence: 98%
“…the initiation of therapy. In the long-term, STEIROPOULOS et al [41] reported significant improvements in systemic inflammatory markers, including total lymphocyte counts, CD4+ cells, tumour necrosis factor (TNF)-a levels and uric acid levels after 6 months in patients with good compliance to CPAP therapy; however, no such improvements were identified in patients with poor compliance. In contrast, KOHLER et al [35] did not find any differences in systemic inflammatory markers, highsensitive C-reactive protein (CRP), plasma IL-6, interferon-c, and adiponectin levels between patients receiving therapeutic and sub-therapeutic CPAP treatments for 4 weeks.…”
Section: Sleep-related Disorders MD Alahmari Et Almentioning
confidence: 99%